2012
DOI: 10.1371/journal.pone.0042759
|View full text |Cite
|
Sign up to set email alerts
|

Association of Betel Nut with Carcinogenesis: Revisit with a Clinical Perspective

Abstract: Betel nut (BN), betel quid (BQ) and products derived from them are widely used as a socially endorsed masticatory product. The addictive nature of BN/BQ has resulted in its widespread usage making it the fourth most abused substance by humans. Progressively, several additives, including chewing tobacco, got added to simple BN preparations. This addictive practice has been shown to have strong etiological correlation with human susceptibility to cancer, particularly oral and oropharyngeal cancers.The PUBMED dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
203
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(207 citation statements)
references
References 158 publications
(195 reference statements)
2
203
2
Order By: Relevance
“…Of several factors that are implicated for these cancers, consumption of raw betel-nut (RBN; Areca catechu L.), instead of dry betel-nut, appears to be highly relevant besides the use of tobacco and alcohol (IARC monograph 1985). In the State of Meghalaya, the variety of Areca nut, locally called 'kwai', is raw, unprocessed with higher contents of alkaloids, polyphenol and tannins as compared to the dried one (Sharan, 1996). The betel-quid used in Meghalaya contains RBN, lime paste and small portion of betel-leaf without tobacco and other constituents.…”
Section: Introductionmentioning
confidence: 99%
“…Of several factors that are implicated for these cancers, consumption of raw betel-nut (RBN; Areca catechu L.), instead of dry betel-nut, appears to be highly relevant besides the use of tobacco and alcohol (IARC monograph 1985). In the State of Meghalaya, the variety of Areca nut, locally called 'kwai', is raw, unprocessed with higher contents of alkaloids, polyphenol and tannins as compared to the dried one (Sharan, 1996). The betel-quid used in Meghalaya contains RBN, lime paste and small portion of betel-leaf without tobacco and other constituents.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies from the northeast India reported tobacco smoking as one of the strongest risk factor for HNC (Yadav et al, 2010;Talukdar et al, 2013;Choudhury and Ghosh, 2014;Ghosh et al, 2014a) . Moreover, it was seen that tobacco-betel quid chewing also had a very high impact on HNC risk (Sharan et al, 2012;Choudhury et al, 2014) . Tobacco in any form generates free radicals that deplete antioxidants and cause oxidative damage to DNA, proteins and lipids resulting in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Human cytochrome P450, family 1, subfamily A, polypeptide 1 (CYP1A1) is one of the major phase I enzymes, involved in the activation of carcinogens related to head and neck cancers, such as polycyclic aromatic hydrocarbon (PAH), heterocyclic amines, N-nitrosamine, alkaloids, polyphenols and tannins present in tobacco smoke and betel quid (Wu et al, 2004;Sharan et al, 2012). Ethanol and acetaldehyde of alcoholic drinks are important chemical agents related to various cancers (Lachenmeier et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Alkaloids, polyphenols and tannins are the active components of betel nut. Habituated or prolonged use of betel nut may lead to carcinogenic transformation of cells, and there is much evidence to suggest that these effects are associated with increased risk for the development of oral squamous cell carcinoma (OSCC) [108].…”
Section: Smokeless Tobaccomentioning
confidence: 99%
“…Earlier epidemiological studies reported that habituated use of betel nut or betel quid with or without tobacco (such as "gutkha") is directly linked with increased HNSCC risk, more particularly oral carcinoma [108]. Zhou et al [109] in New England conducted a population based case control study to evaluate the relationship between smokeless tobacco use and the risk of HNSCC for a total of 1046 cases and 1239 frequency matched controls, and reported that individuals who used smokeless tobacco for more than ten years had high risk of developing HNSCC [109].…”
Section: Smokeless Tobaccomentioning
confidence: 99%